Pengaruh Model Pembelajaran Problem Based Learning Terhadap Peningkatan Keterampilan Berpikir Kritis dan Kreatif Pelajaran Matematika - Hidayat, Taufik; Sucipto, Sucipto; Hanifah, Sri Yuni (Jurnal Ilmiah Wahana Pendidikan, 2024)
This quantitative study investigated the influence of the problem-based learning (PBL) model on the enhancement of critical and creative thinking skills in mathematics. The population of this study comprised all students at SMK Negeri 3 Pamekasan, with a sample of 36 students from class XI PPLG 1 as the experimental group and 35 students from class XI PPLG 2 as the control group. Random sampling was employed as the sampling technique. Data was collected using pre-test and post-test instruments for critical thinking skills, consisting of 20 multiple-choice questions, and a creative thinking questionnaire with 20 statements. Data analysis involved validity testing, reliability testing, homogeneity testing, normality testing, and a T-test, all analyzed using SPSS. Based on the T-test results in Table 1) the average pre-test score for critical thinking skills in the control group was 53.71, and in the experimental group, it was 51.39. The significance value (2-tailed) was 0.521 > 0.05, indicating acceptance of the null hypothesis (H0) and rejection of the alternative hypothesis (H1). However, after the post-test, the average score for the control group was 66.00, and for the experimental group, it was 80.14. The significance value (2-tailed) was 0.000 < 0.05, indicating rejection of H0 and acceptance of H1. There is an influence of the use of problem based learning models on improving critical and creative thinking skills.